SOCIOLOGY OF KNOWLEDGE IN TIMES DETERMINED BY KNOWLEDGE - BARANOWSKI, MARIUSZ (Society Register, 2019)
This article is a selective introduction to the description and characterization of the changes that have occurred in the sociology of knowledge since the publication of Max Scheler’s book in 1924 to contemporary times, most often conceptualized by the term knowledge society. A brief review of the main threads in the field of sociology of knowledge was intended to draw attention to the theoretical and practical advantages of particular approaches, as well as their disadvantages, resulting in a trivial study of the phenomenon of knowledge in question. The descriptive character of this article also allowed for a number of systematizations within specific approaches (e.g. Michel Foucault) and within a broad perspective of the knowledge phenomenon.